Epileptic seizures in intracerebral haemorrhage. Issue 11 (November 1989) - Sung, C Y; Chu, N S
Abstract : Among 1402 patients with intracerebral haemorrhage (ICH), seizures occurred in 64 (4.6%) and epilepsy in 35 (2.5%). Seizure was the first manifestation of ICH in 19 patients (30%). Status epilepticus occurred in 11 patients (17%) and it was the initial presentation of ICH in six (9%). The majority had simple partial seizures that were predominantly focal and motor. There were 38 patients with early seizure and 26 patients with late seizure. Ninety per cent of seizures occurred within one year after ICH. Eleven patients (29%) with early seizure developed epilepsy, whereas 24 patients (93%) with late seizure developed recurrent seizures. The incidence of seizure was 32% for lobar haematoma, 2% respectively for putaminal, thalamic and pontine haemorrhages and 1% for cerebellar haemorrhage. Twenty-six (62%) out of 42 patients with lobar haematomas developed epilepsy. Thirteen patients (34%) with early seizure died within three months after the onset of seizures whereas three patients (12%) with late seizure died within the same period. The majority of patients who died had deep-seated haematomas.